How Can the COVID-19 Pandemic Lead to Positive Changes in Urology Residency? - Busetto, Gian Maria; Del Giudice, Francesco; Mari, Andrea; Sperduti, Isabella; Longo, Nicola; Antonelli, Alessandro; Cerruto, Maria Angela; Costantini, Elisabetta; Carini, Marco; Minervini, Andrea; Rocco, Bernardo; Artibani, Walter; et al. (Frontiers in Surgery, 2020)
The COVID-19 outbreak, in a few weeks, overloaded Italian hospitals, and the majority of medical procedures were postponed. During the pandemic, with hospital reorganization, clinical and learning activities performed by residents suffered a forced remodulation. The objective of this study is to investigate how urology training in Italy has been affected during the COVID-19 era. In this multi-academic study, we compared residents' training during the highest outbreak level with their previous activity. Overall 387 (67.1%) of the 577 Italian Urology residents participated in a 72-h anonymous online survey with 36 items sent via email. The main outcomes were clinical/surgical activities, social distancing, distance learning, and telemedicine. Clinical and learning activity was significantly reduced for the overall group, and after categorizing residents as those working only in COVID hospitals, both “junior” and “senior” residents, and those working in any of three geographical areas created (Italian regions were clustered in three major zones according to the prevalence of COVID-19). A significant decrease in outpatient activity, invasive diagnostic procedures, and endoscopic and major surgeries was reported. Through multivariate analysis, the specific year of residency has been found to be an independent predictor for all response modification. Being in zone 3 and zone 2 and having “senior” resident status were independent predictors associated with a lower reduction of the clinical and learning activity. Working in a COVID hospital and having “senior” resident status were independent predictors associated with higher reduction of the outpatient activity. Working in zone 3 and having “senior” resident status were independent predictors of lower and higher outpatient surgical activity, respectively. Working in a COVID hospital was an independent predictor associated with robotic surgical activity. The majority of residents reported that distance teaching and multidisciplinary virtual meetings are still not used, and 44.8% reported that their relationships with colleagues decreased. The COVID-19 pandemic presents an unprecedented challenge, including changes in the training and education of urology residents. The COVID era can offer an opportunity to balance and implement innovative solutions that can bridge the educational gap and can be part of future urology training.